DOI: 10.11606/t.5.2009.tde-15062009-143051
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da dispersão da bupivacaína na anestesia peridural em cães

Abstract: AGRADECIMENTOSPrimeiramente e principalmente agradeço a meus pais. Inicialmente por acreditarem na minha capacidade. Mas também por me proporcionarem o período do meu doutoramento em São Paulo. Minha mãe, meu exemplo de garra, luta, aplicação, competência, trabalho e comprometimento. Meu pai, minha figura de sensatez, equilíbrio e centralidade, me ensinou a raciocinar e analisar os aspectos da vida, me ajudando a conduzi-la melhor. Enfim, as razões por eu estar vivo, e querer continuar vivendo.A professora Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0
1

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
2
1
0
1
Order By: Relevance
“…In addition, the decrease in block, with statistical difference, from moment 4 in GP and moment 5 in GD (Figure 3), indicates the return of the block. From these moments, the lidocaine 2% concentration within the epidural space becomes insufficient to promote the block of the most cranial nervous roots, corroborating the results found by Freire (2008).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, the decrease in block, with statistical difference, from moment 4 in GP and moment 5 in GD (Figure 3), indicates the return of the block. From these moments, the lidocaine 2% concentration within the epidural space becomes insufficient to promote the block of the most cranial nervous roots, corroborating the results found by Freire (2008).…”
Section: Resultssupporting
confidence: 85%
“…Therefore, it is possible to rule out the drug-related aspects and the particularities of the patient, since all the animals went through the two groups and received the same drug (lidocaine 2%). It is suggested that the increase in available time observed in GD is due to the higher volume of drug administered, agreeing with Freire (2008) that, when using different volumes of bupivacaine, a larger number of blocked segments was obtained with the application of larger volumes if compared with the smaller ones. This was already expected, since administration of higher amounts of drug triggers greater action.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…As características dos bloqueios epidurais devem ser levadas em consideração para o cálculo da dose para o paciente, além de outros parâmetros, como o peso corporal do animal e o comprimento da coluna vertebral (Freire, 2011;Otero, 2013). O uso do comprimento da coluna vertebral se baseia n o valor em centímetros medidos desde o osso do occipital até a primeira vértebra coccígea (Lumb e Jones, 1973;Almeida et al, 2007;Otero, 2013, Otero et al, 2018.…”
unclassified